Performance and advantages of a soft-core based parallel architecture for energy peak detection in the calorimeter Level 0 trigger for the NA62 experiment at CERN. (14th March 2017) - Ammendola, R.; Barbanera, M.; Bizzarri, M.; Bonaiuto, V.; Ceccucci, A.; Checcucci, B.; Simone, N. De; Fantechi, R.; Federici, L.; Fucci, A.; Lupi, M.; Paoluzzi, G.; et al.
Abstract: The NA62 experiment at CERN SPS has started its data-taking. Its aim is to measure the branching ratio of the ultra-rare decay K + → π + ν ν̅ . In this context, rejecting the background is a crucial topic. One of the main background to the measurement is represented by the K + → π + π 0 decay. In the 1-8.5 mrad decay region this background is rejected by the calorimetric trigger processor (Cal-L0). In this work we present the performance of a soft-core based parallel architecture built on FPGAs for the energy peak reconstruction as an alternative to an implementation completely founded on VHDL language.